(untitled) (Zaporizhzhia Historical Review, 2021)
The tax farmings in the towns of Southern Ukraine of the second half XVIII ñ beginning of ХІХ centuries are analyzed in this article. The main varieties of the tax farmings which took place in this region are described. The role of government and local self-government in tax farmings system is found out.